أزدواجية العلاقة بين المرأة والشعر والشعراء في التاريخ الإسلامي (41 – 232هـ/660 – 846م) دراسة تاريخية تحليلة - HASAN, RAMZIYA HAMZA (Journal of Duhok University, 2023)
The research sought to discuss a problem revolving around the nature of the relationship between women, poetry, and poets in a known historical period. It is considered one of the most important and flourishing Islamic eras in terms of thought and culture, As well as economic and social recovery. It is known that Islam came to legislate life, and it has never been known to have erected barriers between what is religious and what is life or urban. Therefore, women in ancient Islamic societies were not isolated from life practices. Rather, it was an integral part of cultural, intellectual, economic and social life, and even its momentum. The research concluded with results that indicate the special methodology followed by Islam in employing a fertile ground for women. With an explanation of the importance of poetry in developing wealth